Zebrafish xenograft model for studying mechanism and treatment of non-small cell lung cancer brain metastasis - Ruo-Yue Fan (BMC, 2021)
Abstract Background Brain metastasis (BM) is thought to be related to the mortality and poor prognosis of non-small cell lung cancer (NSCLC). Despite promising development of NSCLC treatment, the treatment of NSCLC BM is still not optimistic due to the existence of the blood-brain barrier (BBB) that prevent drug penetration, as well as the short median survival time of the patients left for treatment. In this context, further development of quick and effective pre-clinical models is needed in NSCLC BM treatment. Here, we report a model system using zebrafish to promote the development of drugs for patients with NSCLC BM. Methods Three different NSCLC cell lines (H1975, A549 and H1299) were used to establish zebrafish BM models. The embryo age and cell number for injection were first optimized. Metastatic cells were observed in the brain blood vessels of zebrafish and were verified by hematoxylin-eosin (HE) staining. Then, the metastasis potentials of H1975 and A549 with manipulated microRNA-330-3p (miR-330-3p) expression were also investigated. Finally, sensitivities of H1975 and A549 to osimertinib and gefitinib were tested. Results This zebrafish BM model could distinguish NSCLC cell lines with different BM potential. Over-expressed miR-330-p significantly improved the BM potential of the A549 cells while knockdown miR-330-p reduced the BM ability of the H1975 cells. Both osimertinib and gefitinib showed inhibition effect in zebrafish BM model with the inhibition rate higher than 50 %. H1975 cell showed much higher sensitivity to osimertinib rather than gefitinib both in vivo and in vitro. Conclusions We established zebrafish brain metastasis model for studying mechanism and treatment of NSCLC BM. This study provided a useful model for NSCLC brain metastasis that could be used to study the mechanism that drive NSCLC cells to the brain as well as identify potential therapeutic options.